Beyond the production of food: how can nutrition-sensitive agriculture address nutrition challenges? - Sharma, Indu Kumari (Vrije Universiteit Amsterdam, 2023)
Beyond the production of food: how can Nutrition-Sensitive Agriculture address nutrition challenges? Despite substantial strides in reducing poverty over the past five decades in low and middle-income countries (LMICs), these countries experience disproportionately high rates of undernutrition. Agriculture is a key sector that plays a significant role in addressing malnutrition by addressing food insecurity. Particularly promising are nutrition-sensitive agriculture (NSA) interventions, which are agricultural interventions that incorporate a clear objective to improve nutrition and integrate nutrition actions to achieve the nutrition objective, thereby also addressing nutrition security. As a part of the multisectoral response, NSA interventions address multiple underlying causes of malnutrition. However, studies on the mechanisms by which such interventions impact nutrition and which factors influence outcomes are scarce. Therefore, this PhD research aimed to gain insights into the impact pathways of NSA interventions to improve nutritional status, as well as the factors influencing the implementation and sustainability of the interventions in LMICs. This research used a mixed-methods study design that included two systematic reviews and two case studies based on NSA projects implemented in Bangladesh and Lao PDR. In six articles (4 already published), we explain the effects of NSA interventions on nutrition, the pathways to their, and the factors influencing the implementation and sustainability of the interventions. Three chapters demonstrate that NSA interventions can address the multiple determinants of malnutrition, significantly improve diet, reduce micronutrient deficiency, and, to a lesser extent, reduce underweight. This PhD research confirms that NSA interventions can contribute to nutrition through pathways of agricultural production, agricultural income, and women’s empowerment. In addition, this study puts forward the idea of labelling nutrition-related knowledge and behaviour change communication (BCC) as a separate pathway and identifies the strengthening of local institutions as a novel pathway. The dissertation, in three chapters, explains the factors across five domains of implementation research: the outer setting, the inner setting, the characteristics of individuals, the intervention characteristics, and the implementation process. The studies highlight a complex interaction of the factors at multiple levels. Sustaining NSA interventions is challenging due to the complex adaptive features of the food system that make the system both adaptive and resilient. To conclude, transforming agriculture to become more nutritionally sensitive can be impactful in realizing food and nutrition security, but it requires several interrelated strategies across pathways, of which strengthening local institutions, is key.